Analysis of the electric field development and the relaxation of electron velocity distribution function for nanosecond breakdown in air. (29th February 2016) - Hoder, T; Loffhagen, D; Voráč, J; Becker, M M; Brandenburg, R
Abstract: Using theoretical and experimental methods, the electric field and the electron multiplication in direct vicinity of a sharp cathode is analysed. The development of the electric field in the pre-breakdown phase of the atmospheric pressure air negative DC corona discharge in the Trichel pulse regime is determined. During the following ultra-fast electrical breakdown, the emission of selected spectral bands of the nitrogen molecule is recorded with high spatiotemporal resolution using the time-correlated single photon counting method. The emission of a Townsend discharge is used to calibrate the setup for the quantitative determination of electric field. Therefore, the Trichel pulse corona and Townsend discharge cell are arranged in the same single-table setup. This direct calibration procedure is described step-by-step including the discussion of known limitations. Finally, the electric field development of the positive streamer passing the 160 μ m distance in less than two nanoseconds is determined. Due to the high spatiotemporal gradients of the electric field strength within the streamer breakdown, the local field approximation of the electron component is analysed by investigating numerically the temporal and spatial electron relaxation by means of the solution of the electron Boltzmann equation and Monte Carlo simulation. Results of these computations are given for several reduced electric field values and prove that the electrons are in a hydrodynamic equilibrium state for experimentally given space and time scales for reduced fields above 100 Td.